Low-dose caffeine administered in chewing gum does not enhance cycling to exhaustion - Ryan, E. J.; Kim, C. -H.; Muller, M. D.; Bellar, D. M.; Barkley, J. E.; Bliss, M. V.; Jankowski-Wilkinson, A.; Russell, M.; Otterstetter, R.; Macander, D.; Glickman, E. L.; Kamimori, G. H. (The Journal of Strength and Conditioning Research, 2012)
Low-dose caffeine administered in chewing gum does not enhance cycling to exhaustion. The purpose of the current investigation was to examine the effect of low-dose caffeine (CAF) administered in chewing gum at 3 different time points during submaximal cycling exercise to exhaustion. Eight college-aged (26 ± 4 years), physically active (45.5 ± 5.7 ml/kg/min) volunteers participated in 4 experimental trials. Two pieces of caffeinated chewing gum (100 mg per piece, total quantity of 200 mg) were administered in a double-blind manner at 1 of 3 time points (-35, -5, and +15 minutes) with placebo at the other 2 points and at all 3 points in the control trial. The participants cycled at 85% of maximal oxygen consumption until volitional fatigue and time to exhaustion (TTE) were recorded in minutes. Venous blood samples were obtained at -40, -10, and immediately postexercise and analyzed for serum-free fatty acid and plasma catecholamine concentrations. Oxygen consumption, respiratory exchange ratio, heart rate, glucose, lactate, ratings of perceived exertion, and perceived leg pain measures were obtained at baseline and every 10 minutes during cycling. The results showed that there were no significant differences between the trials for any of the parameters measured including TTE. These findings suggest that low-dose CAF administered in chewing gum has no effect on TTE during cycling in recreational athletes and is, therefore, not recommended.